The Effectiveness of Technology-Enhanced Learning Tools in English Language Education - Yosafat Tabasi; Irsan Bertinus Tondowala; Marissa Swanda Tupamahu; Fries Pileman Soa'e Sigilipu; Kadek Ayu Kartika Septiana (Departement of Mathematics Education, 2024)
The integration of technology into English language education has revolutionized traditional teaching methods, offering new avenues for language acquisition and cultural understanding. This literature-based article explores the effectiveness of technology-enhanced learning tools in English language education, focusing on their impact on student engagement, proficiency, and cultural competence. Through a comprehensive review of existing research, the article examines the factors influencing the success of these tools and discusses practical implications for educators and policymakers. Key findings suggest that technology-enhanced learning tools have the potential to enhance student engagement and motivation, personalize learning experiences, and provide access to authentic language use and cultural contexts. However, challenges such as unequal access to technology and the need for effective pedagogical integration remain significant considerations. The article concludes with recommendations for optimizing the use of technology in English language education to maximize its benefits and address existing challenges.